Investment harmonization : the state of play and its potential impacts - Hendy, Françoise L. M. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2006)
Argues that the preoccupation of the proponents of the Caribbean Community (CARICOM) Investment Regime with the creation of a new class of corporate entity having exclusive rights to benefit from investment harmonization in the single market based on the application of an 'ownership and control' test does not serve to facilitate business.